Praktik Isbal di Kalangan Muslim Kontemporer: Kajian Empiris atas Pemahaman Hadis Larangan Isbal - Riza Arif Mz; Nasrullah Nasrullah; Ulfa Maskanah (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2026)
This article aims to understand the isbal contained in thehadiths of the Prophet and give birth to the phenomenon ofdress itself among the people. Thus, the focus is on how thehadiths of the Prophet provide information about isbal and itsmeaning. In addition, bangaimana responds to phenomenathat occur in the community. The description of this articleshows that Isbal is the behavior of lengthening clothingbeyond the ankles. The isbal controversy was born because ofthe existence of substantive contradictory hadiths of theProphet. The hadith that advocates and forbids gives birth todifferences in views and meanings of isbal itself. Therefore, the understanding of Isbal hadith must use the approach ofcontradictory hadiths which in Islamic treasures is referred toas the science of mukhtalif al-ḥadis. Sociologically-anthropologically, claim truth is a fundamental factor in thecontroversy over the practice of dressing with isbal. Keywords: Hadis about isbal